Pengaruh Akuntabilitas, Transparansi, dan Partisipasi Masyarakat Terhadap Pengelolaan Anggaran Pendapatan Dan Belanja Desa Tamansatriyan, Kecamatan Tirtoyudo, Kabupaten Malang - Husna, Fifi Lailatul; Wahono, Budi; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine "The Effect of Transparency Accountability and Community Participation on the Management of the Revenue and Expenditure Budget in Tamansatriyan Village, Tirtoyudo District, Malang Regency". The type of research used in this research is quantitative research. This research sample was taken using sampling techniques sampel purposive sampling using the Slovin formula and obtained results from 99 respondents. The analysis techniques used in this research include validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis test, f test, t test and coefficient of determination test (R2). The research results show that the results of the t test (partial) on accountability, transparency and community participation have a partial effect on the management of village income and expenditure budgets. Meanwhile, the research results show that the results of the F test (simultaneous) on accountability, transparency and community participation simultaneously influence the management of village income and expenditure budgets. Keywords: Accountability, Transparency, Community Participation, Management Of Village Revenue And Expenditure Budgets.